ANALYSIS OF COMPETENCY DEVELOPMENT POLICY IN IMPROVING EMPLOYEE PERFORMANCE AT THE SIROMBU DISTRICT OFFICE - Ainil Mawaddah Zalukhu; Meiman Hidayat Waruwu; Sukaaro Waruwu; Fatolosa Hulu (LPPM YPITI, 2026)
ABSTRACT This study aims to analyze the competency development policy implemented to improve employee performance at the Sirombu Sub-district Office. The research method used is qualitative with data collection techniques through in-depth interviews with relevant employees. The results of the study indicate that the implemented competency development policy has had a positive impact on improving employee performance, although several obstacles were still found such as limited resources and a lack of structured training. The conclusion of this study is that the competency development policy needs to be strengthened with more consistent training support and regular evaluations so that employee performance can continue to improve significantly. The results of the study indicate that the sub-district office has improved training and competency development programs and conducted regular monitoring to ensure the effectiveness of the implemented policies.